Neoadjuvant, anthracycline-free chemotherapy with carboplatin and docetaxel in triple-negative, early-stage breast cancer: a multicentric analysis of rates of pathologic complete response and survival. (3rd May 2016) - Kern, Peter; Kalisch, Anne; von Minckwitz, Gunter; Pütter, Carolin; Kolberg, Hans-Christian; Pott, Dirk; Kurbacher, Christian; Rezai, Mahdi; Kimmig, Rainer
Abstract : Introduction: Triple-negative breast cancer (TNBC) has the highest mortality rates of all subtypes. Anthracycline and taxane regimens yield unsatisfactorily low rates of pathologic complete response (pCR) and are often not feasible in cardiac comorbidity. This study seeks to increase pCR and survival by introducing platin agents. Patients and Methods: In this multicentric, open-label study with six cycles of docetaxel (75 mg/m 2 ) and carboplatin AUC 6 q3w, patients were unwilling or unsuitable for anthracycline-based regimens. Primary endpoint was pCR (ypT0/ypTis ypN0) and survival. Results: pCR rate was 50%. After 2 and 5 years, overall survival (OS) was 96.7 and 89.7%, disease-free-survival (DFS) 96.7 and 85.7%, DDFS 96.7 and 89.6%. Grade 3/4 toxicities were rare. Ninety-three per cent of patients completed six cycles. No toxicity-related treatment discontinuation or febrile neutropaenia was recorded. Conclusion: This regimen is highly effective and feasible in TNBC and may be combined with anthracyclines.